Study of Marine Particles Using Submersible Digital Holographic Camera during the Arctic Expedition - Victor Dyomin; Igor Semiletov; Denis Chernykh; Elena Chertoprud; Alexandra Davydova; Nikolay Kirillov; Olga Konovalova; Alexey Olshukov; Aleksandr Osadchiev; Igor Polovtsev (Applied Sciences, 2022)
The paper presents the results of in situ studies of marine particles of different nature using a submersible digital holographic camera (DHC) during the Arctic expedition. It also describes the features, performance specifications, and possibilities of the DHC and the DHC technology. The DHC technology can be used for noninvasive automatic evaluation of spatial and temporal characteristics of plankton, including the distribution of plankton concentrations. The comparison of quantitative analysis of zooplankton net samples and classification results using the DHC revealed that the error of the DHC classification of mesoplankton at the level of the main systematic orders was about 30%. The results of determining the data on the medium, such as water turbidity, according to the radiation shielding factor (degree) by the particles of the Suspension taxon using the DHC technology are presented; the prospects for studying the size of gas bubbles and their volume content according to the Bubble taxon data are shown. The use of holographic data for in situ point estimates is considered.